From Reformasi to Retrenchment: Media Ownership, Political Power, and Public Voice in Post-1998 Indonesia - Chairullah, Emir (Hasanuddin University, 2025)
When the political system in Indonesia underwent a transition from authoritarianism to democracy at the beginning of the 1998 reform, there was a significant growth in number of mass media across the country. These mass media brought a variety of information and perspectives unpresented in the previous regime. Indonesians also hoped that these mass media organisations could voice their aspirations and act as watchdogs in overseeing government performance. However, the freedom granted by the state to the public and private sector to establish mass media organisations was not as expected. Through literature studies and direct experience as a journalist, the author elaborates on how the mass media in Indonesia during the Reformation era became controlled by conglomerates who prioritised their business and political interests. This article also reveals how President Joko Widodo used conventional media to perpetuate his power. This study’s findings explain how the public abandoned conventional media and turned to social media to obtain information and voice their aspirations. As a result, mass media increasingly lost readers and viewers, making businesses increasingly reluctant to advertise their products.